Strategi Guru Bahasa Indonesia Dalam Menghadapi Lemahnya Minat Belajar Pendidikan Bahasa Indonesia Pada Siswa Kelas 8 SMPN 1 Bontonompo Selatan (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the Indonesian teacher's strategy in dealing with the weak interest in learning Indonesian in grade 8 students of SMPN 1 Bontonompo Selatan. The research instruments in this study were observation, interviews and documentation. The data sources used in this study are primary and secondary data sources. The approach in this study is a qualitative descriptive approach. Data collection techniques are documentation guidelines, interview guidelines, and observation guidelines. Data analysis techniques are the identifying stage, the classifying stage, the analyzing stage, and the describing stage. The research results obtained from this study are: the strategies used by Indonesian teachers in dealing with weak interest in learning Indonesian language education in grade 8 SMPN 1 Bontonompo Selatan using three strategies namely conducting diagnostic tests, using various media and methods and establishing cooperation between teachers and parents of students. This strategy is the choice of Indonesian language teachers in dealing with students' weak interest in learning to increase student motivation and interest in learning.